2017
DOI: 10.1016/j.sdentj.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the position of mental foramen and frequency of anterior loop in Saudi population. A retrospective CBCT study

Abstract: Our sample population most commonly exhibited MF below the apex of 2nd premolar with linear IAC pattern. AL was regarded as the least common pattern in Saudi population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
63
5
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 24 publications
12
63
5
7
Order By: Relevance
“…In our study, the MF was found to be symmetrical in the majority of the samples, which is in agreement with the results reported by others. 14,15,24,26,28 However, they found that position 4 was the most common position to be symmetrical, followed by position 3 whereas in this study, position 3 was the most symmetrical position followed by position 4.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In our study, the MF was found to be symmetrical in the majority of the samples, which is in agreement with the results reported by others. 14,15,24,26,28 However, they found that position 4 was the most common position to be symmetrical, followed by position 3 whereas in this study, position 3 was the most symmetrical position followed by position 4.…”
Section: Discussionmentioning
confidence: 61%
“…Racial and gender differences have been reported in the literature. 11,13,15 Previous studies on the MF location in White North American, British and Turkish populations found that the MF was located in line with the first premolar. In Asians, the MF was located in line with the second premolar where as in Africans, the location was posterior to second premolar.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the literature, the position of the MF was investigated in different ways and populations. Budhiraja et al ( 2 ), Udhaya et al ( 6 ), and Ilayperuma et al ( 7 ) evaluated it on dry skulls, while others used different radiographic techniques like panoramic ( 8 - 10 ) and CBCT ( 3 , 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%